2000
DOI: 10.1080/713654958
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency interferes with proliferation and maturation of cells in the chicken small intestine

Abstract: 1. The effect of vitamin A on the small intestine was examined in vitamin-A-deficient meat-type chickens. 2. Maturation and activity of the small intestinal cells were assayed by detection of proliferating cells with proliferating cells nuclear antigen, goblet cells with Alcian blue, mature cells with alkaline phosphatase and extent of RNA expression with dot blot analysis. 3. Vitamin A deficiency caused hyperproliferation of enterocytes, a decrease in the number of goblet cells, decreased alkaline phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 27 publications
1
32
0
5
Order By: Relevance
“…This result may suggest that the duodenum mucosa of birds fed whole-grain sorghum suffered more damage than in the other treatments, because crypt depth increases according to epithelium turnover needs (Macari, 1995;Boleli et al, 2002). Despite the energy losses with cell turnover, this response may be beneficial to the (Uni et al, 1998;Uni et al, 2000). Broilers fed ground corn presented the shallowest crypts in jejunum (p<0.05) compared to those fed whole-grain sorghum.…”
Section: Resultsmentioning
confidence: 99%
“…This result may suggest that the duodenum mucosa of birds fed whole-grain sorghum suffered more damage than in the other treatments, because crypt depth increases according to epithelium turnover needs (Macari, 1995;Boleli et al, 2002). Despite the energy losses with cell turnover, this response may be beneficial to the (Uni et al, 1998;Uni et al, 2000). Broilers fed ground corn presented the shallowest crypts in jejunum (p<0.05) compared to those fed whole-grain sorghum.…”
Section: Resultsmentioning
confidence: 99%
“…The rates of enterocyte proliferation and migration are affected by a variety of factors. An overt nutrient deficiency, most notably for zinc [80], vitamin A [85], and cyanocobalamin (B12) [95], will affect intestinal physiology. Glutathione is a crucial antioxidant in the gastrointestinal mucosa that is also formed from glutamine [55,72].…”
Section: Early Malnutrition On Development Of the Gastrointestinal Tractmentioning
confidence: 99%
“…Although vitamin A has been reported to play an important role in poultry growth performance (19), our results showed that the average body weight values of female and male quails before and after the study did not differ significantly (Table 3). The absence of a body weight change after supplementation with retinol and retinol esters in this study indicates that the vitamin level in the raw feed materials that constituted the basal diet was adequate for the body weight.…”
Section: Discussionmentioning
confidence: 57%